Clinical features and treatment of vulvar Merkel cell carcinoma: a systematic review. Issue 1 (December 2017) - Nguyen, Austin; Tahseen, Ahmed; Vaudreuil, Adam; Caponetti, Gabriel; Huerter, Christopher
Abstract Background Merkel cell carcinoma is a rare and aggressive neoplasm originating from mechanoreceptor Merkel cells of the stratum basale of the epidermis. Cases affecting the vulva are exceedingly rare, with the currently available literature primarily in case report form. Body Systematic review of the PubMed database returned 17 cases of Merkel cell carcinoma affecting the vulva. Patients presented at a mean age of 59.6 years with a firm, mobile vulvar mass. Symptoms of pain, erythema, pruritus, edema, and ulceration have been reported. Tumor histology is consistent with that of neuroendocrine tumors and typical Merkel cell carcinomas. Neuroendocrine and cytokeratin immunostains are frequently utilized in histopathological workup. Surgical management was the unanimous first-line therapy with adjuvant radiation in most cases. Recurrence occurred in 70.6% of patients at a mean follow-up of 6.3 months. Mortality was at 47.0% at a mean of 7.8 months after initial operation. Conclusion Merkel cell carcinoma affecting the vulva is an extremely rare and highly aggressive neoplasm. The present review of published cases serves to comprehensively describe the clinical course and treatment approaches for vulvar Merkel cell carcinoma.